Dampak Pembangunan Infrastruktur terhadap Pertumbuhan Ekonomi Kota Semarang - Mahroji, Dwi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
ABSTRACT. This study aims to determine the effect of infrastructure development on economic growth in Semarang City. The data used in this study are secondary data in the form of time series data from 2010-2019 period consisting of constant price GRDP data, electricity, water and transportation data in Semarang City. This study uses quantitative descriptive analysis and multiple linear regression. The software used is SPSS 24.0. The results of this study indicate that electricity infrastructure and water infrastructure have a significant influence on economic growth in Semarang City with a significant value of 0.000 <0.05. While Electricity Infrastructure partially has a positive and significant influence on economic growth significant value = 0.000 <0.05 and water infrastructure partially has a positive and significant effect on economic growth with a significant value = 0.000 <0.05. From the results of the study it is concluded that infrastructure development has a very important role in increasing and encouraging economic growth in a region, the development that occurs can have a good impact on the process of economic activity. Especially for transportation infrastructure must be studied by another model of economy..